1998
DOI: 10.1021/je9702955
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Volumes and Viscosities of 1-Propanol + Ethylene Glycol, + Ethylene Glycol Monomethyl, + Ethylene Glycol Dimethyl, + Diethylene Glycol Dimethyl, + Triethylene Glycol Dimethyl, + Diethylene Glycol Diethyl, and + Diethylene Glycol Dibutyl Ethers at 298.15 K

Abstract: Excess molar volumes and viscosities η have been measured as a function of composition for binary liquid mixtures of 1-propanol, C3H7OH, with ethylene glycol (1,2-ethanediol), HOC2H4OH, ethylene glycol monomethyl ether (2-methoxyethanol), CH3OC2H4OH, diethylene glycol dimethyl ether (bis(2-methoxyethyl) ether), CH3(OC2H4)2OCH3, triethylene glycol dimethyl ether (1,2-bis(2-methoxyethoxy)ethane), CH3(OC2H4)3OCH3, and diethylene glycol diethyl ether (bis(2-ethoxyethyl) ether), C2H5(OC2H4)2OC2H5, at 298.15 K. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 8 publications
10
21
0
1
Order By: Relevance
“…Therefore, the packing effect for the negative values of the obtained V E is creditable for alcohol + polymer systems. For the excess molar volume in the 1-propanol + ethylene glycol, + ethylene glycol monomethyl, + ethylene glycol dimethyl, + diethylene glycol dimethyl, + triethylene glycol dimethyl, + diethylene glycol diethyl, and + diethylene glycol dibutyl ethers systems the negative values are reported at 298.15 K . This behavior of discrepancy of V E values with temperature is similar to the studied systems in this study.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, the packing effect for the negative values of the obtained V E is creditable for alcohol + polymer systems. For the excess molar volume in the 1-propanol + ethylene glycol, + ethylene glycol monomethyl, + ethylene glycol dimethyl, + diethylene glycol dimethyl, + triethylene glycol dimethyl, + diethylene glycol diethyl, and + diethylene glycol dibutyl ethers systems the negative values are reported at 298.15 K . This behavior of discrepancy of V E values with temperature is similar to the studied systems in this study.…”
Section: Resultssupporting
confidence: 86%
“…In all MD simulations, we used the modified TrAPPE united-atom (UA) force-field introduced by Fischer et al [ 42 , 43 ], which has been thoroughly validated through extensive comparisons of its predictions for several material properties (density, mean square radius-of-gyration, self-diffusion coefficient, dynamic structure factor, etc.) of low and high molecular weight linear and ring PEO melts with published simulation [ 44 ] or experimental [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] data and/or the predictions of other force fields reported in the literature [ 53 ]. The simulations were executed with the GROMACS [ 54 ] simulation software in the isothermal–isobaric (NPT) statistical ensemble by applying the Nosé–Hoover thermostat [ 55 , 56 ] coupled with the Parrinello–Rahman [ 57 ] barostat to keep the temperature T and the pressure P fixed at the desired values ( T = 413 K and P = 1 atm).…”
Section: Molecular Model and Simulated Systemsmentioning
confidence: 99%
“…Other experimental or theoretical studies of the physical properties of glymes or glyme-containing mixtures can be found in the literature: optical anisotropies of monoglyme, diglyme, triglyme and tetraglyme, 82 excess heat capacities of liquid mixtures of triglyme and tetraglyme with cyclohexane as well as tetraglyme with n-heptane at 288.15, 298.15 and 308.15 K and at atmospheric pressure, 83 weak self-association of glymes based on the evaluation of excess isobaric thermal expansion of glyme and alkane mixtures by an associated mixture model with equation of state contribution, 84 excess molar volumes and excess molar isobaric heat capacities of glymes and ethyl acetate, 44 excess molar volumes and viscosities of glyme and acetonitrile, 85 excess thermodynamic and equilibrium properties of glyme-n-alkane mixtures, 45,65,66,71,81 isobaric vapor-liquid equilibrium for the binary systems of monoglymes and alcohols, 53 excess molar volumes of binary mixtures of glymes and 1propanol, 59,60,63 a calorimetric study of interactions between glyme and alcohol, 61 dynamic viscosities of mixtures of refrigerant (HFC-134a) + glyme at different temperatures and pressures, 86 excess molar enthalpies of mixtures of methanol or triuoroethanol + glyme, 87,88 static relative permittivities of the ternary system of 2-methoxyethanol + 1,2-dimethoxyethane + water from À10-80 C, 78 vapor-liquid equilibrium of binary systems consisting of monoglyme with toluene, methylcyclohexane, or (triuoromethyl)benzene, 69 solubility of HFC-134a refrigerant in glymes, 89 densities, viscosities, and refractive indices of diglyme + cyclohexane or + 1,2,3,4-tetrahydronaphthalene, 70 excess molar heat capacities of mixtures of glymes and various alkanes, 79 and excess heat capacities of glymedimethylsiloxane systems at 25 C, 90 etc. López et al 91 estimated the densities, isothermal compressibilities, and isobaric thermal expansion coefficients of glymes in the temperature range 293.15 K-353.15 K at pressures up to 100 MPa from the PcT data (c is the speed of sound in glyme), and found that the indirect predictions matched the direct experimental values.…”
Section: Diglymementioning
confidence: 99%